1998
DOI: 10.1097/00007890-199812270-00039
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Expression of T Helper 2 Cytokines and Altered Expression of T Helper 1 Cytokines in Long-Term Allograft Survival Induced by Intrathymic Immune Modulation With Donor Class I Major Histocompatibility Complex Peptides1,2

Abstract: These observations demonstrate that acute graft rejection in this model is associated with the expression of Th1 cytokines, IL-2, and IFN-gamma, whereas long-term survival is associated with predominant expression of Th2 cytokines, IL-4, and IL-10. The expression of IFN-gamma in long-surviving allografts in the absence of IL-2 provides evidence for altered activation of the Th1 response in this intrathymic immune modulation model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 49 publications
2
23
1
Order By: Relevance
“…Tolerant hosts mounted potent antidonor proliferative responses and demonstrated anti-donor cytotoxic T cell frequencies that were equivalent to naive animals. Additionally, our results of intragraft cytokine elaboration patterns contrast those observed in tolerant recipients following anti-CD4 mAb therapy which is IL-4 predominant [34], or following intrathymic inoculation of class I allopeptides which induces dichotomized reduction of Th1 (IL-2 and IFN-γ) and predominant Th2 (IL-4 and IL-10) patterns [40]. Allochimeric conditioned recipients demonstrated predominant elaboration of IL-10, but not IL-4, and downregulation of Th1 (IL-2 and IFN-γ) cytokines.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Tolerant hosts mounted potent antidonor proliferative responses and demonstrated anti-donor cytotoxic T cell frequencies that were equivalent to naive animals. Additionally, our results of intragraft cytokine elaboration patterns contrast those observed in tolerant recipients following anti-CD4 mAb therapy which is IL-4 predominant [34], or following intrathymic inoculation of class I allopeptides which induces dichotomized reduction of Th1 (IL-2 and IFN-γ) and predominant Th2 (IL-4 and IL-10) patterns [40]. Allochimeric conditioned recipients demonstrated predominant elaboration of IL-10, but not IL-4, and downregulation of Th1 (IL-2 and IFN-γ) cytokines.…”
Section: Discussioncontrasting
confidence: 73%
“…This strategy has previously suggested that the polymorphic sequences on the α 1 -helical regions RT1.A u and RT1.A l included immunogenic epitopes that induced accelerated rejection of RT1 u and RT1 I cardiac allografts in RT1 b recipients [25]. In concert with previous studies that utilized synthetic peptides derived from the polymorphyic RT1.A a regions [12,14] [24,39,40]. Further, pre-transplant peripheral administration of syngeneic dendritic cells (DCs) pulsed with immunogenic donor peptide (100 μg/ml) has induced robust peripheral tolerance [43][44][45].…”
Section: Discussionmentioning
confidence: 97%
“…5A). The major role of the active form of IL-12 (p70 IL-12) is to promote the differentiation of naive CD4 + T cells into Th1 cells, a cell type which is critically involved in acute allograft rejection [29]. A recent report from Viera et al [30] describes a new immunosuppressive compound, glatiramer acetate, which acted by favoring Th2 development through both inhibition of p70-IL12 secretion and enhanced IL-10 production.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely proposed that Th1 cells promote allograft rejection and hinder tolerance induction, whereas Th2 responses favor a state of tolerance. These hypotheses come largely from the fact that, in multiple models, acute allograft rejection has been associated with the local presence of type 1 cytokine proteins or mRNA transcripts, whereas lack of rejection has correlated with the presence of type 2 cytokines (2)(3)(4). In addition, treatment with anti-IL-12 to prevent type 1 differentiation has resulted in prolonged allograft survival when acute rejection was dependent on indirect presentation of allopeptides or in the case of minor Ag-mismatched allografts (5).…”
mentioning
confidence: 99%